CHEMICAL PROPERTIES AND PHYSICAL FRACTIONS OF ORGANIC MATTER IN OXISOLS UNDER INTEGRATED AGRICULTURAL PRODUCTION SYSTEMS - de Moraes Rego, Carlos Augusto Rocha; Oliveira, Paulo Sérgio Rabello de; Piano, Jeferson Tiago; Egewarth, Jonas Francisco; Egewarth, Vanessa Aline; López de Herrera, Juan; Gonçalves Junior, Affonso Celso (REVISTA DE AGRICULTURA NEOTROPICAL, 2020)
The main cause of decreased soil fertility and soil organic matter content is intensive crop farming with inadequate management. This study aimed to evaluate soil chemical properties, total organic carbon content, physical granulometric fractions (particulate organic carbon and mineral-associated organic carbon), carbon stocks, and carbon management indices of oxisols in different integrated agricultural production systems (IAPSs) with reference to values in a haymaking area and native forest. The experiments were performed using completely randomized design, considering nine differently managed areas, including seven IAPSs and two reference areas (haymaking area and native forest); four soil samples from the 0.00-0.05, 0.05-0.10, and 0.10-0.20 m layers were randomly collected from each area and the abovementioned variables were evaluated. The results showed no differences in variables between the managed and reference areas, indicating the maintenance of fertility and carbon fractions. Therefore, the tested management strategies promote beneficial modifications of soil properties. Producers should adopt different IAPS management strategies for soil preservation.